Building crack monitoring based on digital image processing (Fracture and Structural Integrity, 2020)
Building crack monitoring is of great value to the judgment of building safety. In this study, the digital image processing technology was studied and applied to the monitoring of building cracks. Crack images were collected by CCD camera, and then operations such as graying, correction, denoising and segmentation were carried out to obtain clear crack images. The obtained images are processed morphologically to further improve the quality. Finally, the width and length of cracks are calculated. In the case analysis, the results of 15 cracks measured by microscope were taken as the standards and compared with the calculated results. The results showed that the results calculated in this study and the manual measurement results differed little, and the average error of the width and length is 0.021 mm and 0.024 mm respectively, which suggested that the method proposed had high reliability. The findings of this study provides a new idea for the further development of building crack monitoring field, which is conducive to the accurate assessment of building safety.
Keywords: Digital image processing; building crack; monitoring; histogram equalization